Extended Pelagic Life in a Bathybenthic Octopus - Villanueva, Roger; Laptikhovsky, Vladimir V.; Piertney, Stuart B.; Fernández-Álvarez, Fernando Ángel; Collins, Martin A.; Ablett, Jonathan D.; Escánez, Alejandro (Frontiers in Marine Science, 2020)
Planktonic stages of benthic octopuses can reach relatively large sizes in some species, usually in oceanic, epipelagic waters while living as part of the macroplankton. These young octopuses appear to delay settlement on the seabed for an undetermined period of time that is probably longer than for those octopus paralarvae living in coastal, neritic waters. The reason for this delay is unknown and existing information about their biology is very scarce. Here we report on the presence of juvenile and subadult forms of the bathybenthic octopus Pteroctopus tetracirrhus in oceanic waters of the South and North Atlantic and its association with the pyrosomid species Pyrosoma atlanticum, apparently used by the octopus as a refuge or shelter. The relatively large size of the P. tetracirrhus living in oceanic waters as the individuals reported here, together with the morphological characteristics of this bathybenthic species including its gelatinous body, minute suckers embedded in swollen skin and the deep interbrachial web, indicates that P. tetracirrhus may be considered a model of a transitional octopus species that is colonizing the pelagic environment by avoiding descending to the bathyal benthos. This process seems to occur in the same way as in the supposed origin of the ctenoglossan holopelagic octopods of the families Amphitretidae, Bolitaenidae, and Vitreledonellidae, which have arisen via neoteny from the planktonic paralarval stages of benthic octopuses.